2012
DOI: 10.1152/ajpheart.00250.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D2 rescues size and function of GATA4 haplo-insufficient hearts

Abstract: Transcription factor GATA4 is a key regulator of cardiomyocyte growth, and differentiation and 50% reduction in GATA4 levels results in hypoplastic hearts. Search for GATA4 targets/effectors revealed cyclin D(2) (CD2), a member of the D-type cyclins (D(1), D(2), and D(3)) that play a vital role in cell growth and differentiation as a direct transcriptional target and a mediator of GATA4 growth in postnatal cardiomyocytes. GATA4 associates with the CD2 promoter in cardiomyocytes and is sufficient to induce endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
7
26
0
Order By: Relevance
“…1D, CycD2 was enriched twofold on the −99 GATA site relative to the Dessert gene (used as internal control). GATA4 was also enriched at this site, consistent with our previous results (18).…”
Section: Significancesupporting
confidence: 93%
See 3 more Smart Citations
“…1D, CycD2 was enriched twofold on the −99 GATA site relative to the Dessert gene (used as internal control). GATA4 was also enriched at this site, consistent with our previous results (18).…”
Section: Significancesupporting
confidence: 93%
“…Quantitative PCR analysis confirmed that ccnd2 transcripts are specifically up-regulated in the heart but have no effect on GATA4 encoding mRNA levels (Fig. 1C), consistent with our published results (18). Up-regulation of ccnd2 resulted in a twofold higher GATA-dependent luciferase transcription specifically in the heart of double transgenics but not in other organs exhibiting GATA activity like liver (Fig.…”
Section: Significancesupporting
confidence: 90%
See 2 more Smart Citations
“…Cyclin D2 is a GATA4 cofactor in cardiogenesis (54); however, we did not observe any changes in cyclin D2 expression. In the neonatal heart, GATA4 induces cyclin D2 transcription (55). In our study, reduced GATA4 expression does not cause cyclin D2 downregulation.…”
Section: Discussionsupporting
confidence: 42%